2014
DOI: 10.1039/c4cc00440j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of nitrogen and sulfur co-doped graphene as efficient metal-free electrocatalysts for the oxygen reduction reaction

Abstract: Novel N, S co-doped graphene (NSG) was prepared by annealing graphene oxide with thiourea as the single N and S precursor. The NSG electrodes, as efficient metal-free electrocatalysts, show a direct four-electron reaction pathway, high onset potential, high current density and high stability for the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
170
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 308 publications
(180 citation statements)
references
References 15 publications
10
170
0
Order By: Relevance
“…6b), close to that of the reported metal-free electrocatalysts such as NSG700. 19 With the disc and ring currents in the LSV curve, the electron transfer number (n) per oxygen molecule involved in the ORR was calculated from the following equation:…”
Section: Electrochemical Properties Analysismentioning
confidence: 99%
“…6b), close to that of the reported metal-free electrocatalysts such as NSG700. 19 With the disc and ring currents in the LSV curve, the electron transfer number (n) per oxygen molecule involved in the ORR was calculated from the following equation:…”
Section: Electrochemical Properties Analysismentioning
confidence: 99%
“…S6) before and after acid leaching showed that the -C-S-C-covalent bond can be stable in the acid solution. According to previous studies, -C-S-C-is beneficial for enhancing the catalytic activity of ORR [60,61]. The high-resolution Fe 2p spectrum of PmPDA-GR-Fe (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…However, the dual doping could bring out high asymmetric spin density of C atoms, which plays a much more important role than the atomic charge density in determining the catalytic active sites. or thermal reaction of graphene oxide and solid/gaseous N/S-containing precursors 21,63 (e. g., thiourea or NH 3 /H 2 S gas). The synergistic effect between heteroatoms was also reported for N and S dual-doped graphene, which is eneficial for improving the RR or example, Qiao"s group displayed a very high ORR onset potential of NSG (−0.06 V vs. Ag/AgCl), very close to that of commercial Pt/C (−0.03 V vs.…”
Section: N B-doped Graphenementioning
confidence: 99%